Hubungan Antara Risiko Pekerjaan Manual Handling, Usia, dan Masa Kerja Dengan Risiko Gangguan Sistem Muskuloskeletal Pada Pekerja Bagian Perakitan Penulangan Besi Beton Di PT Wijaya Karya Beton Tbk. Boyolali - Pratama, Dimas Hendra; , Tarwaka, PGDip Sc, M.Erg; , Dr. Suwaji, M.Kes (2015)
Musculoskeletal system problem is skeletal muscles disturbance affecting a person ranging from very mild to severe complaints. This condition can also be exacerbated by posture of working such as unnatural body posture, workload, as well as individual factors (age and years of service). Workers of concrete steel assembly perform activity of lift-transport handling manually. Purpose of the study is to know correlation between risk of manual handling work, age, and tenure and risk of musculoskeletal system disturbances. It is an analytical-observational research with cross sectional approach. Sample of the research is 32 workers of lift-haul manual handling taken by using total sampling technique. Data analysis of the research uses Spearman-Rho with a significant level (α = 0.05). Results of Spearman-Rho showed a significant correlation between risk of manual handling jobs and risk of musculoskeletal system disturbances (p = 0.031) (r = 0.382) with a weak correlation and indicated a direction of positive correlation meaning that the higher the risk of manual work handling, the greater the risk of musculoskeletal system disorders. A significant correlation between age and risk of musculoskeletal system disorders (p = 0.018) (r = 0.413) with fairly strong and positive direction correlation meaning that the older age, the higher the risk of musculoskeletal system disturbance. While no correlation was found between tenure and the risk of musculoskeletal system disorder (p-value = 172).